Mukhamandapa or the principal porch of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the main entrance (facing west) of the Mahanaleshwar Temple. The mukhamandapa (front porch) is square in design and of a semi-open variety. The two front pillars are supporting the cantilevered projection. The pillars are surrounded by dwarf walls on two sides that have kakshasanas (seat backs) on them.